ANDROGEN DISBALANCE IN GOUTY ARTHRITIS IN MEN WITH OBESITY - Kapustianska, A.A. (World of Medicine and Biology, 2014)
We established pathogenetic role of testosterone in the development and progression of gouty arthritis and obesity in men. It is proved that the aggravation of gouty arthritis is accompanied by changes in testosterone levels, depending on the degree of obesity. We find a strong link between the concentration of testosterone and uric acid, as well as stage of disease. It is shown that obesity contributes to the development of degenerative changes in osteo-articular apparatus in violation of motor function. In turn, promotes the development of gouty arthritis, overweight and obesity.
Keywords: gout; obesity; testosterone